The Effect of Using The Jakarta Post Newspaper Articles In Enhancing Vocabulary of English For University Students: An Experimental Research - Rohmatillah, Rohmatillah (Universitas Islam Negeri Raden Intan Lampung, 2016)
The objectives of this research are to know and to describe about the effect of using Jakarta Post newspaper articles in enhancing vocabulary of English for university students. The research methodology used was quasi experimental research. In this research the population was the first semester of English Education program at IAIn Raden Intan Lampung. The sample of the research was two clasess consisting of 31 students for experimental class and 30 students for control class. In the experimental class was taught by using The Jakarta Post newspaper article, meanwhile in the control class was taught by using textbook. In collecting the data, the researcher used vocabulary test in form of multiple choice test. The test was being tryout. After the test was valid and reliable, the researcher gave pre test to the experimental and control class. After conducting three treatments, the reseacher conducted post test for both clasess to know the students progress before and after treatments. From the data analysis, it was found that the result of data analysis computed by using SPSS , the result showed that p value was 0.001 < α = 0.05, it means that Ha is accepted, and Ho rejected. In addition based on the result of the research that was conducted at IAIN, the researcher concluded that there is significant effect of using the Jakarta Post newspaper articles to enhance vocabulary of English for university students.